Experimental verification of suitability of insulation testing rig in determining thermophysical properties of insulating materials. Issue 1 (1st January 2019) - Nnamchi, S. N.; Nnamchi, O. A.; S. Odebiyi, O.; Edosa, O. O.; Wanazusi, T.
Abstract: Verification of suitability of insulation testing rig (ITR) in determining the thermophysical properties of insulating materials (IM) is strongly based on the measurement of temperatures on the inner/outer surfaces of the insulators (white cotton fabric, molded ash, molded rice husk and molded sawdust), outer surface of mild steel, and the temperatures of the external/internal heat transfer fluids (air/water). The dimensionless excess temperature (heat rejection factor(HRF)) was determined as the ratio of IM to mild steel excess temperature. Thermal balance on the IM led to mechanistic thermal equation whose coefficient yielded the insulation parameter, which is synonymous with the fin parameter. The thermal conductivity of the insulators was uniquely determined as a function of HRF, geometric shapes of the insulator/mild steel, and the internal/external fluid properties. Distinctively, the thermal diffusivity was determined as function of rate of dimensionless excess temperature and the insulation parameter rather than as ratio of thermal conductivity to thermal storage capacity. Essentially, the thermal conductivity determined for the above-mentioned IM were; 0.0597, 0.0377–0.0555, 0.0251–0.0344 and 0.0110–0.0293 W/mK, respectively. The thermal diffusivity obtained for the aforementioned IM were; 3.443, 1.3008–1.9302, 1.0384–1.4418 and 0.2499–0.8384 m 2 /s, respectively. The empirical results produced the numerical values of the four cardinal thermophysical properties, which unanimously agreed with the established results in literature. This agreement substantiates the fact that ITR is quite suitable in determining the thermophysical properties of future insulators. Therefore, this study strongly endorses the application of ITR for characterization and development of fibrous agricultural wastes as insulators.